Fabrication of nickel-cobalt intermetallic nanotapes by electrospinning - Noor Athirah, Ismail (2016)
This dissertation thesis is on the fabrication of Nickel-Cobalt nanotapes prepared by electrospinning technique. Electrospinning is a nanofabrication technique in which a polymeric solution is allowed to pass through an electric field of intensity ~105 V/m. In this work, the precursor polymeric solution was prepared by dissolving equimolar nickel acetate (18 mmol) and cobalt acetate in 50 wt.% polyvinylpyrrolidone (Mol. Wt. 40,000) in ethanol. The viscosity of the above solution was measured using a viscometer; the viscosity of the solution was ~653 cP. This solution was electrospun using a commercial electrospinning unit at 24 kV with a solution injection rate 0.5 ml/h. The as-spun fibers were annealed in an argon atmosphere at ~450 – 550oC for 1 h, based on thermogravimetric analysis. The annealed materials were examined by X-ray diffraction (XRD) technique and field emission scanning electron microscopy (FESEM). The XRD measurements showed that the annealed samples were only partially crystallized and has a belt-like morphology.